The Italian geography of regional resilience: The role of cooperative firms - Michele Costa; Flavio Delbono (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2021)
We investigate the economic resilience of the Italian regions between 2008 and 2019. We then calculate some indices of resistance as well as recovery for both real GDP per capita and employment. We show that during (and after) recessions such indices follow different patterns and the Southern regions perform worse than the rest of the country. Then we try to detect if and how the composition of employment relates to regional resilience. We show that the size of the cooperative employment improves the overall resilience of regional employment, especially during recoveries. We also show and explain that this is not the case with cooperative added value as related to the resilience of regional GDP. Overall, the cooperative movement seems to positively contribute to the resilience of regional economies, supporting an inclusive growth especially through the employment channel.
Keywords: E32; J54; L21; R11; 330; macroeconomic shock; regional economies; employment; cooperative movement